Reevaluating evidence of density-dependent growth in northern fur seals ( Callorhinus ursinus ) based on measurements of archived skeletal specimens - Etnier, Michael A (Canadian Journal of Fisheries and Aquatic Sciences, 2004)
Analysis of length-at-age measurements of archived skeletal material shows that somatic growth rates of male northern fur seals (Callorhinus ursinus) vary inversely with population density. Von Bertalanffy growth curves were estimated for two series of known-age mandibles collected 19111920 (n = 156) and 19401953 (n = 151), time periods representing the historic population minimum and maximum, respectively. Mandibles from the former time period are larger than mandibles from the latter time period, suggesting a density-dependent response in somatic growth. Although density-dependent growth in northern fur seals has been suggested before, previous studies have been hampered by the potentially confounding factors of fisheries interactions, variable environmental conditions, and harvest of adult female northern fur seals. The material analyzed here pre-dates the substantial development of the Bering Sea groundfish fishery and the period of heaviest culling of females. Likewise, the two time periods examined are characterized by broadly similar climatic and environmental conditions. Therefore, the results support the hypothesis that measurements of somatic growth rates provide an index of population levels relative to carrying capacity. Growth rate studies could therefore be used to evaluate the current population status of northern fur seals.